Analysis of serum natalizumab concentrations obtained during routine clinical care in patients with multiple sclerosis: A cross-sectional study - Moskorova, D; Kacirova, I; Hradilek, P; Matlak, P; Brozmanova, H; Kusnierova, P; Licha, K; Sistik, P; Koristkova, B; Grundmann, M (Multiple sclerosis and related disorders, 2025)
BACKGROUND: Natalizumab is a humanized monoclonal antibody administered at a fixed dose of 300 mg intravenously or subcutaneously every 4-6 weeks to treat relapsing-remitting multiple sclerosis. In this prospective cross-sectional study, natalizumab serum concentrations obtained during routine healthcare were measured, and the relationships between different routes of administration, sampling times, body characteristics, changes in blood count, and presence of anti-natalizumab antibodies were evaluated. METHODS: Ninety-two patients were included in this study. Blood samples were collected 0-48 days after administration, and natalizumab serum and anti-natalizumab antibody concentrations, as well as blood counts were measured. Subsequently, patients were divided into three groups according to the collection time after natalizumab administration. RESULTS: During the entire monitored period, serum natalizumab concentrations ranged from 1.8 to 193.3 µg/mL and 1.8 to 100.3 µg/mL after intravenous and subcutaneous administrations, respectively. A significant inverse correlation was found between serum natalizumab concentrations and differential and absolute peripheral blood neutrophil counts, erythrocyte counts, and hemoglobin concentrations. CONCLUSION: Although all patients were treated with the same dose, a 30-fold difference in serum natalizumab concentrations was observed. This wide inter-individual variability can potentially lead to an increased risk of natalizumab adverse events or, conversely, suboptimal therapeutic concentrations with the risk of further worsening of multiple sclerosis.
Keywords: dospělí; natalizumab; Female; Natalizumab; Adult; mladý dospělý; ženské pohlaví; průřezové studie; Serum concentrations; relabující-remitující roztroušená skleróza; imunologické faktory; lidé; Multiple Sclerosis; roztroušená skleróza; prospektivní studie; Cross-Sectional Studies; Male; Immunologic Factors; Prospective Studies; Multiple Sclerosis, Relapsing-Remitting; Young Adult; Therapeutic drug monitoring; lidé středního věku; mužské pohlaví; Multiple sclerosis; Middle Aged; Humans